PENGARUH LINGKUNGAN KERJA, KOMPETENSI DAN KOMPENSASI TERHADAP KINERJA PETUGAS REKAM MEDIS RSU HAJI SURABAYA - jurnalmap map (Program Pascasarjana Universitas Wijaya Putra Surabaya, 2022)
Performance is the result of work that someone has achieved in carrying out work activities. High performance officer called an employee or employees who are productive, vice versa officers who do not meet the standards are said to be unproductive. The performance of the officer's medical record can be measured from a patient's rekmed document preparation of promptness, thoroughness of medical record document and complete the task with the right time which is already specified. Some of the factors that affect the working environment i.e. kinera both physical and non-physical, the officer's competence, as well as adequate compensation given to employees is in compliance. This research aims to analyze the influence of work environment, competence and compensation on performance Clerk medical record RSU Haji Surabaya. This research using medical record clerk 46 outpatient units working in RSU Haji Surabaya. The source data used using the questionnaire then analyzed with the SPSS data processing. The variables used in this study is the work environment, Competence & compensation as free variables, the performance of the officer's medical record as a variable. The results of this research show that the working environment variables do not affect performance significantly to outpatient medical record officers partially or simultaneous. Variable competence and significant effect on performance Compensation officer medical record either partially or simultaneous